2016
DOI: 10.1111/vsu.12434
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Mesh for Obliteration of the Nephrosplenic Space in Horses: 26 Clinical Cases

Abstract: Mesh obliteration of the nephrosplenic space is an effective alternative to suture closure for preventing nephrosplenic entrapment of the large colon in horses. No complications related to mesh obliteration were reported in our study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…Although NSE appears to have low mortality, the long‐term survival of horses with NSE has neither been well defined, nor is it known how clinical factors influence time to death. With the potential for recurrence, surgical techniques to close the nephrosplenic space have been described . However, the success of closure of the nephrosplenic space in reducing recurrence has not been compared to a reference cohort of horses with NSE that have not had closure of the nephrosplenic space.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although NSE appears to have low mortality, the long‐term survival of horses with NSE has neither been well defined, nor is it known how clinical factors influence time to death. With the potential for recurrence, surgical techniques to close the nephrosplenic space have been described . However, the success of closure of the nephrosplenic space in reducing recurrence has not been compared to a reference cohort of horses with NSE that have not had closure of the nephrosplenic space.…”
mentioning
confidence: 99%
“…With the potential for recurrence, surgical techniques to close the nephrosplenic space have been described. 3,15,[19][20][21][22][23] However, the success of closure of the nephrosplenic space in reducing recurrence has not been compared to a reference cohort of horses with NSE that have not had closure of the nephrosplenic space.…”
mentioning
confidence: 99%
“…A large number of horses included in this study had shown mild colic signs that were treated medically or resolved spontaneously without definitive diagnosis. LDDLC has also been associated with chronic weight loss and inappetence 28 29 . Furthermore, a previous study by Röcken et al 12 reported cases of LDDLC with none or very mild clinical signs.…”
Section: Discussionmentioning
confidence: 98%
“…In this retrospective study, Megan Burke and Eric Parente report surgical complications, occurrence of post‐obliteration colic, long‐term outcome, and return to previous function for horses treated with prosthetic mesh obliteration of the nephrosplenic space .…”
Section: Nephrosplenic Space Obliteration Using Prosthetic Meshmentioning
confidence: 99%